All animals are equal but some animals are more equal than others: Plasma lactate and succinate in hemorrhagic shock—A comparison in rodents, swine, nonhuman primates, and injured patients. Issue 3 (March 2018) - Reisz, Julie A.; Wither, Matthew J.; Moore, Ernest E.; Slaughter, Anne L.; Moore, Hunter B.; Ghasabyan, Arsen; Chandler, James; Schaub, Leasha J.; Fragoso, Miguel; Nunns, Geoffrey; Silliman, Christopher C.; Hansen, Kirk C.; et al.
Abstract : BACKGROUND: Plasma levels of lactate and succinate are predictors of mortality in critically injured patients in military and civilian settings. In relative terms, these metabolic derangements have been recapitulated in rodent, swine, and nonhuman primate models of severe hemorrhage. However, no direct absolute quantitative comparison has been evaluated across these species. METHODS: Ultra-high pressure liquid chromatography-mass spectrometry with stable isotope standards was used to determine absolute concentrations of baseline and postshock levels of lactate and succinate in rats, pigs, macaques, and injured patients. RESULTS: Baseline levels of lactate and succinate were most comparable to humans in macaques, followed by pigs and rats. Baseline levels of lactate in pigs and baseline and postshock levels of lactate and succinate in rats were significantly higher than those measured in macaques and humans. Postshock levels of lactate and succinate in pigs and macaques, respectively, were directly comparable to measurements in critically injured patients. CONCLUSION: Acknowledging the caveats associated with the variable degrees of shock in the clinical cohort, our data indicate that larger mammals represent a better model than rodents when investigating metabolic derangements secondary to severe hemorrhage.